1993
DOI: 10.2307/3869431
|View full text |Cite
|
Sign up to set email alerts
|

MsERK1: A Mitogen-Activated Protein Kinase from a Flowering Plant

Abstract: The induction of proliferation and differentiation in cultured mammalian cells is mediated by a cascade of protein phosphorylations. A key enzyme in this signaling pathway is mitogen-activated protein (MAP) kinase (or ERK, extracellular signal-regulated kinase). We report the recovery of a full-length cDNA clone encoding a MAP kinase from alfalfa. We have named the 44-kD protein encoded by this clone MsERK1. Recombinant MsERK1 (rMsERK1), when overexpressed in Escherichia coli, is recognized by antibodies raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…For example, other plant protein kinases, such as tobacco protein kinases NPK5 and calcium-dependent protein kinase (CDPK), that apparently do not belong to the MAP kinase family are known to phosphorylate MBP and/or synthetic peptides derived from MBP (47,48). Although many cDNAs that encode putative members of the MAP kinase family have been isolated from various plants (5)(6)(7)(8)(9)(10), the characteristics of the active forms of the corresponding proteins have not yet been examined. Recently, novel kinases called SAPKs or JNKs, which have been grouped in a MAP kinase subfamily on the basis of their amino acid sequences, have been isolated from mammalian cells, but they failed to phosphorylate MBP (49,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, other plant protein kinases, such as tobacco protein kinases NPK5 and calcium-dependent protein kinase (CDPK), that apparently do not belong to the MAP kinase family are known to phosphorylate MBP and/or synthetic peptides derived from MBP (47,48). Although many cDNAs that encode putative members of the MAP kinase family have been isolated from various plants (5)(6)(7)(8)(9)(10), the characteristics of the active forms of the corresponding proteins have not yet been examined. Recently, novel kinases called SAPKs or JNKs, which have been grouped in a MAP kinase subfamily on the basis of their amino acid sequences, have been isolated from mammalian cells, but they failed to phosphorylate MBP (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Signal pathways known as mitogen-activated protein (MAP) kinase cascades have been established recently in yeasts and animals and shown to be involved in various physiological processes (1)(2)(3)(4). Furthermore, several groups including our own have shown that plants also have homologs of the components of the MAP kinase cascade (5)(6)(7)(8)(9)(10)(11)(12). Thus, it would seem likely that MAP kinase cascades occur in plants even though the relationships among these plant homologs have yet to be determined (13).…”
mentioning
confidence: 99%
“…Many plant genes encode receptor kinases sharing the same basic domain structures as shown in animal receptors and are called RLKs. 1 Plant RLKs are involved in diverse processes such as hormone response (7), mitogenic induction (8), self-incompatibility (9), shoot meristem development (10), and disease resistance (11). Expression studies have implicated RLKs to be involved in embryogenesis, pollen function, and light responses (12).…”
mentioning
confidence: 99%
“…However, it is unclear whether this antibody also recognizes alfalfa MMK1. MMK1 is a member of another distinct group of plant MAP kinase represented by SIPK from tobacco (20,28,29). MMK1 shares 8 of 10 C-terminal amino acids with MMK4.…”
mentioning
confidence: 99%